(untitled) (Journal of International Studies, 2020)
The relationship between Islam and democracy can be viewed based on the participation of Islamic movement in the democratic process through election. This democratization of Islamic movement became more significant in early 1990s when authoritarian governments accepted democracy and introduced the multi-party system. The Islamic movement and Muslims have accepted democracy as the channel to obtain legal political means because some of the principles of democracy such as justice, freedom and equality are embodied in (syura) in Islamic politics. For further discussion on the democratization of Islamic movement, this paper explores several factors that influence Islamic movement to participate in the democratic process through election.